The law of the Executive branch : presidential power - Fisher, Louis (New York : Oxford University Press, 2014)
This title places the law of the executive branch firmly in the context of constitutional language, framers' intent, and more than two centuries of practice. Each provision of the US Constitution is analyzed to reveal its contemporary meaning and in concert with the application of presidential power.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on February 28, 2014).
Keywords: Presidents -- United States; Executive power -- United States; War and emergency powers -- United States